FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN PEMBIAYAAN DI INDONESIA - Hasan Ruspandi; Rusdayanti Asma (Universitas Lambung Mangkurat, 2014)
This study aims to determine the factors that influence the profitability of financing company in Indonesia with samples of 6 companies listed in Indonesia Stock Exchange 2007-2012 period that meets the provisions of the Minister of Finance Regulation No. 84/PMK.012/2006 about a company financing. Return on Assets and Return on Equity is used as a proxy for profitability. Debt to Equity Ratio, Net Receivables Assets, Operating Efficiency, Size and Growth used as a measure of internal factors and the Gross Domestic Product as macroeconomic factors. The results showed the condition of the financing company experienced a difficult situation in making a profit from the provision of financing receivables. The use of debt and cost efficiency to provide benefits to shareholders, while the company size and growth of assets does not affect profitability. Macroeconomic factors found to influence the profitability of financing companies